Developing a Reporting Guideline for Social and Psychological Intervention Trials - Montgomery, Paul (American Public Health Association, 2013)
Understanding randomized controlled trials of complex social and psychological interventions requires a detailed description of the interventions tested and the methods used to evaluate them. However, randomized controlled trial reports often omit, or inadequately report, this information. Incomplete and inaccurate reporting hinders the optimal use of research, wastes resources, and fails to meet ethical obligations to research participants and consumers. We explain how reporting guidelines have improved the quality of reports in medicine, and describe the ongoing development of a new reporting guideline for randomized controlled trials: an extension of the Consolidated Standards of Reporting Trials for social and psychological interventions. We invite readers to participate in the project by visiting our Web site, to help us reach the best-informed consensus on these guidelines (http://tinyurl.com/consort-study).